Modelling herbicides movement in railway embankments in Germany - Lúcia Pedrosa; Sabrina Michael; Martin Sonntag; Markus Zingelmann; Traugott Scheytt (Journal of Contaminant Hydrology, 2026)

Numerical study of water content distribution and controlling factors in and beneath a railway embankment - Lúcia Pedrosa; Christian Engelmann; Martin Binder; Sabrina Michael; Markus Zingelmann; Traugott Scheytt (Grundwasser, 2026)
As urbanization and transport demands rise, railway systems face higher risks from operational disruptions due to system failures and climate-related impacts, especially in urban areas. Understanding water flow and distribution beneath railway embankments is crucial not only for assessing potential contaminant transport in soil and groundwater but also for identifying possible structural weaknesses. This study implements numerical simulations to investigate these dynamics, focusing on a standard railway embankment designed according to German norms. The model setup includes ballast, a low-permeability protection subgrade surface layer (PSS), a subgrade (embankment base), and a subsurface to a depth of 10 m. Numerical simulations were conducted following a univariate approach. Variation parameters included key hydraulic characteristics of the embankment and subsurface. Further parameters were groundwater recharge rate, groundwater level, existence of a less permeable horizontal layer at multiple depths, and thickness of the embankment. The most sensitive parameters shaping water percolation fronts are identified as empirical coefficients (especially the Van Genuchten shape variable α), groundwater levels and hydraulic conductivity. The results indicate that the PSS layer retains the greatest amount of water from the rail system, particularly beneath the ballast. Low α values (0.8 m –1 to 7.7 m –1 ) led to total retention of water within the embankment, with no visible percolation fronts and the lowest values observed at the PSS layer. Shallow groundwater increased initial water content up to 0.30 at the PSS layer, rapidly approaching near fully water-saturated conditions. Embankments with low hydraulic conductivities (0.048 m d −1 to 1.207 m d −1 ) show the highest water contents, reaching up to 0.46, forming a clogging area prone to retain contaminants.

Urbanisation and habitat shape resource-driven dietary shifts in wild birds - Marion Chatelain; Oskar Rennstam Rubbmark; Johannes Rüdisser; Michael Traugott (Landscape and Urban Planning, 2026)

Trap crops enhance the control efficacy of Metarhizium brunneum against a soil-dwelling pest - Michael Brunner; Christiane Zeisler; Diane Neu; Claire Rotondo; Oskar R. Rubbmark; Lara Reinbacher; Giselher Grabenweger; Michael Traugott (Journal of Pest Science, 2024)
Soil-dwelling insect pests may cause considerable damage to crops worldwide, and their belowground lifestyle makes them hard to control. Amongst the most promising control agents for subterranean pests are soilborne entomopathogenic fungi (EPF) such as Metarhizium brunneum . Albeit EPF can be highly pathogenic to their target pest species under laboratory conditions, their efficacy in the field is often limited due to adverse environmental conditions. Here, we test for the first time if the efficacy of EPF can be improved when they are augmented with trap crops. In a field experiment, the M. brunneum strain ART2825 was combined with a trap crops mixture of six plant species and evaluated for its control effect of wireworms (Coleoptera: Elateridae). When both were combined in the main crop, potato damage was lowered on average by 42.5% and wireworm abundance by 50.8%. Single application of trap crops or EPF lowered damage/pest abundance only by 29.9%/15.89% and 34.7%/4.77%, respectively. Importantly, the strength of the synergistic pest control effect between trap crops and EPF increased disproportionately with increasing wireworm abundance. However, DNA-based gut content analysis showed that wireworms’ feeding preferences were not shifting toward the trap crops. Our findings demonstrate that combining trap crops with EPF improves the efficacy of the latter and leads to a synergistic control effect which magnifies with increasing wireworm abundance. Hence, the synergistic effect of EPF and trap crops might be a promising control strategy for soil-dwelling pests in general and significantly improve our abilities to manage soil pests environmentally friendly.

Functional redundancy of weed seed predation is reduced by intensified agriculture - Eirini Daouti; Veronika Neidel; Benjamin Carbonne; Hana Vašková; Michael Traugott; Corinna Wallinger; Riccardo Bommarco; Benjamin Feit; David A. Bohan; Pavel Saska; Jiří Skuhrovec; Sasha Vasconcelos; et al. (Ecology Letters, 2024)
Intensified agriculture, a driver of biodiversity loss, can diminish ecosystem functions and their stability. Biodiversity can increase functional redundancy and is expected to stabilize ecosystem functions. Few studies, however, have explored how agricultural intensity affects functional redundancy and its link with ecosystem function stability. Here, within a continental‐wide study, we assess how functional redundancy of seed predation is affected by agricultural intensity and landscape simplification. By combining carabid abundances with molecular gut content data, functional redundancy of seed predation was quantified for 65 weed genera across 60 fields in four European countries. Across weed genera, functional redundancy was reduced with high field management intensity and simplified crop rotations. Moreover, functional redundancy increased the spatial stability of weed seed predation at the field scale. We found that ecosystem functions are vulnerable to disturbances in intensively managed agroecosystems, providing empirical evidence of the importance of biodiversity for stable ecosystem functions across space.

Correction: Consumer identity but not food availability affects carabid diet in cereal crops - Yasemin Guenay-Greunke; Harald Trager; David A. Bohan; Michael Traugott; Corinna Wallinger (Journal of Pest Science, 2024)

Consumer identity but not food availability affects carabid diet in cereal crops - Yasemin Guenay-Greunke; Harald Trager; David A. Bohan; Michael Traugott; Corinna Wallinger (Journal of Pest Science, 2024)
Understanding trophic interactions in agroecosystems is crucial for harnessing ecosystem services such as pest control, thus enabling a reduction in pesticide use. Carabid beetles (Coleoptera: Carabidae) have the potential to regulate not only insect pests but also weed seeds and slugs. The aim of this study was to investigate the food choice of different carabid species in the experimental setting of a cereal field with varying seed and slug prey availability during the season. In addition to varying food availability, the effects of species identity and season on carabid food choice should also be closely examined. Therefore, the gut contents of 1,120 beetles of eight carabid species were screened for the DNA of plants, aphids, springtails, earthworms and slugs via diagnostic multiplex PCR and a nested metabarcoding approach for plant species identification. Plant DNA was detected far more often (72%) than the various animal prey types (less than 12.5% each). Within the plant detections, 80 weed species were identified in the metabarcoding, with Galinsoga parviflora/quadriradiata ( Galinsoga spp.—quickweeds) as the most frequently detected species. Carabid food choice was driven by their species identity and seasonality, while no effect of increased availability of seeds and slugs on their food choice was detected. While weed seeds seem to be an important food source for carabids, their availability does not directly affect the carabid diet. The importance of consumer identity and seasonality highlight the need for a diverse carabid species community for resilient pest control services.

Evaluating 87Sr/86Sr and Sr/Ca ratios in otoliths of different European freshwater fish species as fishery management tool in an Alpine foreland with limited geological variability - Andreas Zitek; Johannes Oehm; Michael Schober; Anastassiya Tchaikovsky; Johanna Irrgeher; Anika Retzmann; Bettina Thalinger; Michael Traugott; Thomas Prohaska (Fisheries Research, 2023)

Correction to: Molecular analysis indicates high levels of carabid weed seed consumption in cereal fields across Central Europe - Britta Frei; Yasemin Guenay; David A. Bohan; Michael Traugott; Corinna Wallinger (Journal of Pest Science, 2022)

Fish as predators and prey: DNA ‐based assessment of their role in food webs - Michael Traugott; Bettina Thalinger; Corinna Wallinger; Daniela Sint (Journal of Fish Biology, 2021)
Fish are both consumers and prey, and as such part of a dynamic trophic network. Measuring how they are trophically linked, both directly and indirectly, to other species is vital to comprehend the mechanisms driving alterations in fish communities in space and time. Moreover, this knowledge also helps to understand how fish communities respond to environmental change and delivers important information for implementing management of fish stocks. DNA‐based methods have significantly widened our ability to assess trophic interactions in both marine and freshwater systems and they possess a range of advantages over other approaches in diet analysis. In this review we provide an overview of different DNA‐based methods that have been used to assess trophic interactions of fish as consumers and prey. We consider the practicalities and limitations, and emphasize critical aspects when analysing molecular derived trophic data. We exemplify how molecular techniques have been employed to unravel food web interactions involving fish as consumers and prey. In addition to the exciting opportunities DNA‐based approaches offer, we identify current challenges and future prospects for assessing fish food webs where DNA‐based approaches will play an important role.

Intraguild predation is independent of landscape context and does not affect the temporal dynamics of aphids in cereal fields - Sebastián Ortiz-Martínez; Karin Staudacher; Vera Baumgartner; Michael Traugott; Blas Lavandero (Journal of Pest Science, 2020)

Resilience of ecosystem processes: a new approach shows that functional redundancy of biological control services is reduced by landscape simplification - Benjamin Feit; Nico Blüthgen; Michael Traugott; Mattias Jonsson (Ecology Letters, 2019)
Functional redundancy can increase the resilience of ecosystem processes by providing insurance against species loss and the effects of abundance fluctuations. However, due to the difficulty of assessing individual species’ contributions and the lack of a metric allowing for a quantification of redundancy within communities, few attempts have been made to estimate redundancy for individual ecosystem processes. We present a new method linking interaction metrics with metabolic theory that allows for a quantification of redundancy at the level of ecosystem processes. Using this approach, redundancy in the predation on aphids and other prey by natural enemies across a landscape heterogeneity gradient was estimated. Functional redundancy of predators was high in heterogeneous landscapes, low in homogeneous landscapes and scaled with predator specialisation. Our approach allows quantifying functional redundancy within communities and can be used to assess the role of functional redundancy across a wide variety of ecosystem processes and environmental factors.

Molecular analysis indicates high levels of carabid weed seed consumption in cereal fields across Central Europe - Britta Frei; Yasemin Guenay; David A. Bohan; Michael Traugott; Corinna Wallinger (Journal of Pest Science, 2019)
Carabid beetles are abundant in temperate agroecosystems and can play a pivotal role as biocontrol agents. While there is good knowledge regarding their effects on invertebrate pests in some systems, comparably little is known on the rate of seed feeding under field conditions. Molecular approaches are ideally suited for investigating carabid feeding interactions; to date, however, they have only been applied to animal prey. We sampled adult carabid beetles in organic cereal fields in three regions along a Central European transect. Regurgitates from populations of the three most common species, Poecilus cupreus, Pseudoophonus rufipes and Pterostichus melanarius , were screened for plant DNA, cereal aphids, collembolans and earthworms. The frequency of carabid individuals positive for plant DNA was high (> 70%) and independent of carabid species, sex, region and the time point of sampling. Detections for non-pest and pest prey were comparably lower, with 21.6% for collembolans, 18.1% for earthworms and 4.2% for aphids, respectively. Despite the prolonged detection period of plant DNA in carabid guts, as compared to animal prey, these first results suggest that weed seeds form an important part of the adult carabid diet. It would also lend support to the hypothesis that seed-feeding carabids are biocontrol agents of weeds, with effects of regulation on the weed seedbank that depend on behavioural and contextual factors including carabid species preferences for weed seed species, their life stage and tillage practices.

Introduction: Special issue on species interactions, ecological networks and community dynamics – Untangling the entangled bank using molecular techniques - Tomas Roslin; Michael Traugott; Mattias Jonsson; Graham N. Stone; Simon Creer; William O. C. Symondson (Molecular Ecology, 2019)

Resolving the predator first paradox: Arthropod predator food webs in pioneer sites of glacier forelands - Daniela Sint; Ruediger Kaufmann; Rebecca Mayer; Michael Traugott (Molecular Ecology, 2019)
Primary succession on bare ground surrounded by intact ecosystems is, during its first stages, characterized by predator‐dominated arthropod communities. However, little is known on what prey sustains these predators at the start of succession and which factors drive the structure of these food webs. As prey availability can be extremely patchy and episodic in pioneer stages, trophic networks might be highly variable. Moreover, the importance of allochthonous versus autochthonous food sources for these pioneer predators is mostly unknown. To answer these questions, the gut content of 1,832 arthropod predators, including four species of carabid beetles, two lycosid and several linyphiid spider species caught in early and late pioneer stages of three glacier forelands, was screened molecularly to track intraguild and extraguild trophic interactions among all major prey groups occurring in these systems. Two‐thirds of the 2,310 identified food detections were collembolans and intraguild prey, while one‐third were allochthonous flying insects. Predator identity and not successional stage or valley had by far the strongest impact on the trophic interaction patterns. Still, the variability of prey spectra increased significantly from early to late pioneer stage, as did the niche width of the predators. As such the structure of pioneer arthropod food webs in recently deglaciated Alpine habitats seems to be driven foremost by predator identity while site and early successional effects contribute to a lesser extent to food web variability. Our findings also suggest that in these pioneer sites, predatory arthropods depend less on allochthonous aeolian prey but are mainly sustained by prey of local production.

Identifying plant DNA in the sponging–feeding insect pest Drosophila suzukii - Felix Briem; Christiane Zeisler; Yasemin Guenay; Karin Staudacher; Heidrun Vogt; Michael Traugott (Journal of Pest Science, 2018)

A simple and cost-effective molecular method to track predation on Drosophila suzukii in the field - Sarah Wolf; Christiane Zeisler; Daniela Sint; Jörg Romeis; Michael Traugott; Jana Collatz (Journal of Pest Science, 2018)

Quantifizierung von Fischbeständen mittels eDNA in alpinen Fließgewässern - Bettina Thalinger; Daniela Sint; Christiane Zeisler; Dominik Kirschner; Michael Traugott; Christian Moritz; Richard Schwarzenberger (WASSERWIRTSCHAFT, 2018)

Special issue on Drosophila suzukii: from global invasion to sustainable control - Antonio Biondi; Michael Traugott; Nicolas Desneux (Journal of Pest Science, 2016)

Diagnostic PCR assays to unravel food web interactions in cereal crops with focus on biological control of aphids - Karin Staudacher; Mattias Jonsson; Michael Traugott (Journal of Pest Science, 2016)

Food Web Designer: a flexible tool to visualize interaction networks - Daniela Sint; Michael Traugott (Journal of Pest Science, 2016)

Provenancing fish in freshwaters of the Alpine Foreland using Sr/Ca and 87Sr/86Sr ratios in otoliths and otolith shape parameters - Oehm Johannes; Irrgeher Johanna; Tchaikovsky Anastassiya; Thalinger Bettina; Traugott Michael; Prohaska Thomas; Zitek Andreas (Frontiers in Marine Science, 2015)

A two-step multiplex PCR system identifying Central European fish species - Thalinger Bettina; Oehm Johannes; Mayr Hannes; Zeisler Christiane; Traugott Michael (Frontiers in Marine Science, 2015)

Intraguild predation in pioneer predator communities of alpine glacier forelands - Lorna Raso; Daniela Sint; Rebecca Mayer; Simon Plangg; Thomas Recheis; Silvia Brunner; Rüdiger Kaufmann; Michael Traugott (Molecular Ecology, 2014)
Pioneer communities establishing themselves in the barren terrain in front of glacier forelands consist principally of predator species such as carabid beetles and lycosid spiders. The fact that so many different predators can co‐inhabit an area with no apparent primary production was initially explained by allochthonous material deposited in these forelands. However, whether these populations can be sustained on allochthonous material alone is questionable and recent studies point towards this assumption to be flawed. Intraguild predation ( IGP ) might play an important role in these pioneer predator assemblages, especially in the very early successional stages where other prey is scarce. Here, we investigated IGP between the main predator species and their consumption of C ollembola, an important autochthonous alternative prey, within a glacier foreland in the Ö tztal ( A ustrian A lps). Multiplex PCR and stable isotope analysis were used to characterize the trophic niches in an early and late pioneer stage over 2 years. Results showed that intraguild prey was consumed by all invertebrate predators, particularly the larger carabid species. Contrary to our initial hypothesis, the DNA detection frequency of IGP prey was not significantly higher in early than in late pioneer stage, which was corroborated by the stable isotope analysis. Collembola were the most frequently detected prey in all of the predators, and the overall prey DNA detection patterns were consistent between years. Our findings show that IGP appears as a constant in these pioneer predator communities and that it remains unaffected by successional changes.

How generalist herbivores exploit belowground plant diversity in temperate grasslands - Corinna Wallinger; Karin Staudacher; Nikolaus Schallhart; Evi Mitterrutzner; Eva‐Maria Steiner; Anita Juen; Michael Traugott (Molecular Ecology, 2014)
Belowground herbivores impact plant performance, thereby inducing changes in plant community composition, which potentially leads to cascading effects onto higher trophic levels and ecosystem processes and productivity. Among soil‐living insects, external root‐chewing generalist herbivores have the strongest impact on plants. However, the lack of knowledge on their feeding behaviour under field conditions considerably hampers achieving a comprehensive understanding of how they affect plant communities. Here, we address this gap of knowledge by investigating the feeding behaviour of A griotes click beetle larvae, which are common generalist external root‐chewers in temperate grassland soils. Utilizing diagnostic multiplex PCR to assess the larval diet, we examined the seasonal patterns in feeding activity, putative preferences for specific plant taxa, and whether species identity and larval instar affect food choices of the herbivores. Contrary to our hypothesis, most of the larvae were feeding‐active throughout the entire vegetation period, indicating that the grassland plants are subjected to constant belowground feeding pressure. Feeding was selective, with members of P lantaginaceae and A steraceae being preferred; A piaceae were avoided. Poaceae, although assumed to be most preferred, had an intermediate position. The food preferences exhibited seasonal changes, indicating a fluctuation in plant traits important for wireworm feeding choice. Species‐ and instar‐specific differences in dietary choice of the A griotes larvae were small, suggesting that species and larval instars occupy the same trophic niche. According to the current findings, the food choice of these larvae is primarily driven by plant identity, exhibiting seasonal changes. This needs to be considered when analysing soil herbivore–plant interactions.

Identification of the most common predatory hoverflies of Mediterranean vegetable crops and their parasitism using multiplex PCR - Priscila Gomez-Polo; Michael Traugott; Oscar Alomar; Cristina Castañé; Santos Rojo; Nuria Agustí (Journal of Pest Science, 2014)

Understanding the ecology of wireworms and improving their control: a special issue - Michael Traugott; Nikolaus Schallhart; Karin Staudacher; Corinna Wallinger (Journal of Pest Science, 2013)

Occurrence of Agriotes wireworms in Austrian agricultural land - Karin Staudacher; Nikolaus Schallhart; Peter Pitterl; Corinna Wallinger; Nina Brunner; Marion Landl; Bernhard Kromp; Johann Glauninger; Michael Traugott (Journal of Pest Science, 2013)

Effects of plant identity and diversity on the dietary choice of a soil‐living insect herbivore - Nikolaus Schallhart; Manuel Josef Tusch; Corinna Wallinger; Karin Staudacher; Michael Traugott (Ecology, 2012)
Plant identity and diversity influence herbivore communities in many different ways. While it is well known how they affect the feeding preferences of aboveground herbivores, this information is lacking for soil ecosystems, where examining plant–herbivore trophic interactions is difficult. We performed a mesocosm experiment assessing how plant identity and diversity affect the food choice of Agriotes larvae, which are soil‐living generalist herbivores. We offered four plant species, (maize, a grass, a legume, and a forb) at varying combinations and diversity levels to these larvae, and analyzed their feeding behavior using stable isotopes. We hypothesized that (1) their food choice is driven by preference for certain plant species rather than by root abundance and that (2) the preference for specific plants changes with increasing plant diversity. We found that larvae preferred the grass and legume but avoided maize and the forb. Whether a plant was preferred or avoided was independent of diversity, but the extent of avoidance or preference changed with increasing plant diversity. Our findings reveal that the dietary choice of soil‐living generalist herbivores is determined by plant‐specific traits rather than root abundance. Our data also suggest that soil herbivore feeding preferences are modulated by plant diversity.

Editorial 2012: shaping the profile of Journal of Pest Science - Michael Traugott; Christos Athanassiou; Chris Cutler; Nicolas Desneux; A. Rami Horowitz; Rainer Meyhöfer; Les Shipp; Christian Stauffer; Donald C. Weber; Myron P. Zalucki (Journal of Pest Science, 2012)

Editorial 2010 - Michael Traugott (Journal of Pest Science, 2010)

News from the Editor-in-Chief - Michael Traugott; Jürgen Gross (Journal of Pest Science, 2008)

Detecting predation and scavenging by DNA gut-content analysis: a case study using a soil insect predator-prey system - Anita Juen; Michael Traugott (Oecologia, 2005)